2019
DOI: 10.15390/eb.2019.7315
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Middle School Students’ Attitudes Towards Mathematical Problem-Posing, Attitudes Towards Mathematical Problem-Solving, and Attitudes Towards Mathematics

Abstract: Araştırmada, ortaokul öğrencilerinin matematik problemi oluşturmaya yönelik tutumlarını belirlemek amacıyla bir ölçeğin geliştirilmesi (I. Çalışma), geliştirilen ölçeğin işlerliğinin ortaya konulması ve ortaokul öğrencilerinin matematik problemi oluşturma tutumları, matematik problemi çözme tutumları ve matematiğe yönelik tutumları arasındaki ilişkilerin incelenmesi (II. Çalışma) amaçlanmıştır. I. Çalışmada ölçeğin geçerlik ve güvenirliğine ilişkin kanıtlar ortaya konmuş ve ölçeğin kullanılabilir olduğu göster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…It implies that students were not sure about what they feel when they encounter word problems. These findings contrast with the study conducted by [36] that students enjoy solving word problems. given problem) was ranked as fourth and interpreted as good.…”
Section: Methodscontrasting
confidence: 99%
“…It implies that students were not sure about what they feel when they encounter word problems. These findings contrast with the study conducted by [36] that students enjoy solving word problems. given problem) was ranked as fourth and interpreted as good.…”
Section: Methodscontrasting
confidence: 99%
“…In a study by Fullerton and Kendrick (2013), the ndings revealed that overall, students had a more positive than negative attitude to statistics. Katrancı and Şengül (2019) measured the attitudes toward math problem-solving revealing that students had an overall positive attitude to problem-solving. Mirza and Hussain (2018) determined the attitudes of middle school students to nd that there were no signi cant differences in attitudes between the students.…”
Section: Attitudesmentioning
confidence: 99%
“…Hence, many students prefer dropping the subject altogether. The attitudes that students develop towards the subject guide the behavior of individuals (Katrancı & Şengül, 2019). Positive attitudes lead to better performance where individuals have a better liking for the subject and work harder to achieve better grades (Mirza & Hussain, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was also found that male students were found to be more efficient than females in the case of problem solving [39]. However, other studies indicated that female students had considerably higher problem-solving abilities and a better scientific attitude than male students [40], [41]. In a study, Arslan, Yavuz, and Deringol-Karatas [42] found that female students have significantly better ATPS scores than male students.…”
Section: Introductionmentioning
confidence: 97%